2022
DOI: 10.3389/fimmu.2022.784479
|View full text |Cite
|
Sign up to set email alerts
|

An Immune-Related Gene Signature for Predicting Neoadjuvant Chemoradiotherapy Efficacy in Rectal Carcinoma

Abstract: BackgroundLocally advanced rectal cancers (LARC) show a highly variable response to neoadjuvant chemoradiotherapy (nCRT), and the impact of the tumor immune response in this process is poorly understood. This study aimed to characterize the immune-related gene expression profiles (GEP), pathways, and cell types associated with response or resistance to neoadjuvant chemoradiotherapy.MethodsThe transcriptomic and clinical data of Rectal carcinoma from the Gene Expression Omnibus database and Immune-related genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Five of 20 genes were shown to be predictive in rectal cancer in previous studies. CXCL10, IL12A, CD247 and ITGB1 were identified as predictive markers for the response to neoadjuvant treatment in rectal cancer in previous studies (15,(41)(42)(43)(44)(45). Tumor IRS1 expression was related to the survival of rectal cancer patients (46).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Five of 20 genes were shown to be predictive in rectal cancer in previous studies. CXCL10, IL12A, CD247 and ITGB1 were identified as predictive markers for the response to neoadjuvant treatment in rectal cancer in previous studies (15,(41)(42)(43)(44)(45). Tumor IRS1 expression was related to the survival of rectal cancer patients (46).…”
Section: Discussionmentioning
confidence: 91%
“…Then, intensive or different treatment schemes, as well as different monitoring schemes, can be appropriately selected for these patients. A previous study reported that immune-related genes can be used to predict the response to neoadjuvant therapy (15). However, the relationship between immune-related genes and the long-term prognosis (DFS) of LARC patients receiving neoadjuvant treatment followed by TME and adjuvant chemotherapy is currently unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An increasing number of studies have shown that immune genes can affect radiosensitivity and prognosis by regulating antitumor immune surveillance, antigen presentation and so on. Li et al studied the relationship between gene expression pro les and nCRT response in LARC, and developed a 15-immune gene prediction model to predict the response to nCRT [5]. Carine et al calculated the biopsy-adapted immunoscore (IS B ) based on the in ltration of CD3 + and CD8 + T cells, through which they could predict response to nCRT and better de ne patients eligible to an organ preservation strategy (Watch-and-Wait) [6].…”
Section: Introductionmentioning
confidence: 99%